Covid 19 with Kidney Failure - Arsistya Ayu Marella; Khairun Nisa Berawi; Fitria Saftarina (CV. Jasa Sukses Abadi, 2023)
Corona virus disease 2019 or commonly called COVID-19 is a disease caused by infection with the SARS-CoV-2 virus and is one of the biggest challenges facing humanity in recent years. This disease is highly contagious with various manifestations and complications and poses a threat to public health. This virus can infect a large number of organs, including the lungs and upper respiratory tract, brain, liver, kidneys, intestines and many others. Although the greatest damage occurs in the lungs, the kidneys are no exception, and acute kidney injury (AKI) can occur in patients with COVID-19. AKI is one of the most frequent and serious organic complications of COVID-19. The incidence of COVID-19 AKI. During the COVID-19 pandemic, many patients were hospitalized with severe respiratory illnesses and experienced complications. Acute kidney injury (AKI) is one of the more dangerous complications that contributes to morbidity and mortality among patients. Kidney damage can occur due to direct attack by the virus itself, or due to a cytokine storm caused by an abnormality of the immune system. Hypotension or dehydration, hypoxaemia, sepsis and nephrotoxic drugs can also cause kidney failure. This research method begins by searching articles on Google Scholar, pubmed and ncbi within the year range determined by the researchers and using the keywords COVID-19, kidney failure, complications of kidney failure in COVID-19 patients. The results of the study found articles about producing several conclusions such as the effect of kidney failure on COVID-19 patients, then the long-term effects on the kidneys of patients with COVID-19.